(untitled) (American Journal of Research in Humanities and Social Sciences, 2025)
This research examines the translation of colloquial expressions from Spanish into Arabic in the first season of the popular television series Money Heist, one of the most notable audiovisual works in contemporary Spanish. The study focuses on analyzing and translating culturally and socially charged expressions and exploring the strategies used to preserve their expressive and semantic power. Using a qualitative approach, colloquial expressions were identified and classified, including insults, idiomatic expressions, and vulgar expressions. Their translations were subsequently analyzed, both in the dubbed and translated versions, focusing on techniques such as functional equivalence, euphemism, cultural adaptation, and ellipsis. This paper offers a critical perspective on the importance of maintaining the vernacular in audiovisual translation. It proposes practical recommendations for translators who struggle to convey culturally charged expressions between two languages that differ in structure and style.